2014
DOI: 10.12968/gasn.2014.12.4.32
|View full text |Cite
|
Sign up to set email alerts
|

Assessing support garments in the management of parastomal hernia

Abstract: Many ostomates (people with a stoma) are affected by the complication of a parastomal hernia. The ostomate does not only need to adjust to the stoma but also to the presence of the parastomal hernia and its effect on the stoma function, appliance choice, and skin condition; moreover, it affects the ostomate's ability to manage his/her daily activities. The NHS spends over £1 million in the provision of support garments. While this is a cheaper management option compared with surgery to repair or refashion the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…Limited studies have demonstrated the impact of preventive advice regarding core exercises and support garments (Thompson and Trainor, 2005;North, 2014;Readding, 2014).…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies have demonstrated the impact of preventive advice regarding core exercises and support garments (Thompson and Trainor, 2005;North, 2014;Readding, 2014).…”
Section: Preventionmentioning
confidence: 99%
“…As these changes occur, inevitably there is an increase in appliance use with potential change of stoma product, the introduction to, or increase in, the use of stoma accessories and also the need for a support garment (Cowin and Redmond, 2012;North, 2014;Readding, 2014); all of these are reliant on the delivery of specialist stoma care nursing. Prevention is therefore key but, perhaps more importantly, there is a need for consistency in assessment, with the use of a risk assessment tool to support prevention of parastomal hernias within the provision of stoma care services.…”
mentioning
confidence: 99%
“…The prevention programme in North (2014) indicates potential for immediate post operative exercise when combined with garment support. North (2014) asserts that brand of garment support chosen by the ostomist had no effect on outcome, although expert opinion indicates type of garment is important to achieve optimum outcomes (Readding, 2014). …”
Section: Exercise Advicementioning
confidence: 99%
“…A hernia support garment is thought to alleviate this problem, reducing symptoms and PSH size which makes it less visible through clothing (Williams, 2011;Readding, 2014). However, Cowin and Redmond (2012) showed that although all respondents had ordered a PSH support garment, only 45% regularly wore it, and just 27% thought that wearing a support garment was the best way to manage their stoma.…”
Section: Physical Costmentioning
confidence: 99%
See 1 more Smart Citation